(untitled) (Discourse of Law and Administration, 2021)
In this study, the author undertakes the currently live problem of making some statements by persons affected by the spread of the disease caused by infection with virus SARS-CoV-2 in Poland, who apply for financial support guaranteed by the regulation of the Act of 02nd March 2020 on specific solutions related to preventing, counteracting and combating COVID-19, other infectious diseases and crisis situations caused by them. It is about the statements made under pain of criminal liability for making a false statement, specified in Art. 233 § 6 of Penal code. The author points out that the content of these statements not infrequently requires a prior interpretation of complex regulations of this act, providing practical examples of such regulations. As a result of this, in criminal proceedings conducted in cases concerning the suspicion of making a false statement, a key significance may have the evaluation of the execution in concreto of the subjective features. In the final part of the article, the author discusses effects of the severe sanctions provided for a crime under Art. 233 § 6 of Penal code.